Digital Transformation and Cybersecurity Challenges in Pakistan’s Higher Education Institutions - Soo-jin Choi (Kashmir Journal of Academic Research and Development, 2025)
The pace of digital transformation in higher education around the world has been accelerating as a result of the technology enabling online learning, administrative automation, data analytics and academic collaboration. In Pakistan there is an emerging trend in universities of using digital system of better educational delivery and research capacity and institutional management. However this transformation involves new vulnerabilities for institutions in the form of evolving cybersecurity risks to the privacy of information, availability of services and integrity of academics. This research is carried out to determine the situation concerning digital transformation and associated cybersecurity issues within HEIs of Pakistan. Using a combination of the two methods (n = 420 surveys, n = 20 expert interviews), the study shows a high and high rate of adoption of digital platforms coupled with a pervasive cybersecurity concern, such as phishing attacks, ransomware, insecure networks and lack of security policies. Findings point to interactions between gaps within technical capacity, governance structures and awareness indicating a need for complete cybersecurity structures, training, policy reform and investment in safe infrastructure to sustain digital transformation.
Keywords: Digital transformation; Cybersecurity; Higher education institutions; Pakistan; Digital learning; Data privacy; ICT adoption